Stanovení antioxidaćní aktivity potenciálních scavengerů oxidu dusnatého - Kupková, Z; Cerná, H; Lojek, A; Cíz, M; Benes, L (Ceska a Slovenska farmacie, 2004)
Nitrogen oxide is a relatively stable, highly reactive radical, which develops in the organism by oxidation of the guanidine nitrogen of the amino acid L-arginine by the action of NO-synthase with the development of L-citrulline. It participates in a number of physiological and pathological processes. The difference between the physiological and pathological concentration of nitrogen oxide is very small, and for that reason we search for suitable methods of its determination and the substances influencing the level of nitrogen and thus decreasing its overproduction. Testing of scavenger activity against NO was performed by the method following Griess (spectrophotometric determination of nitrites as the oxidation products of NO), which was compared with the HPLC (high-performance liquid chromatography) method developed by the present authors. The antiradical effect of the compounds being assayed (acetylsalicylic acid, piracetam, paracetamol, serotonin, stobadin dihydrochloride, 5-hydroxy-L-tryptophan, N-acetyl-L-cysteine, L-glutathion, and N-acetyl-DL-penicillamine) against NO was compared with the so-called total antioxidant activity--TRAP (total radical-trapping antioxidant parameter), which corresponds to the capability to trap peroxyl radicals. On the basis of the obtained data, piracetam and acetylsalicylic acid show no antioxidant activity, paracetamol shows probably moderate scavenging action against nitrogen oxide, and other compounds tested (primarily 5-hydroxy-L-tryptophan, serotonin, stobadin) are strong antioxidants against both NO and peroxyl radical.
Keywords: Free Radical Scavengers; Nitric Oxide; antioxidancia; oxid dusnatý; Antioxidants; scavengery volných radikálů